Analysis of The Effectiveness of KCL Polymer on Reactive Clay Formation in The 26 Section of A Field FA1 - Wastu, Apriandi Rizkina Rangga; Husla, Ridha; Ridaliani, Onnie; Suci, Farah Adiana Eka; Soekardy, Mentari Gracia; Azizah, Siti (Testing Center for Oil and Gas LEMIGAS, 2026)
In geothermal well drilling, a primary challenge is clay swelling, particularly in reactive clay formations, where drilling success is largely determined by the type of drilling fluid used. Although gel polymer mud is commonly preferred, adding KCl polymer is often necessary to mitigate swelling in such formations. The study aims to evaluate the effectiveness of KCl-polymer mud in mitigating clay reactivity in the 26-inch borehole section of the FA1 well in a geothermal field. The methodology began with the methylene blue test to assess clay reactivity, followed by the formulation of gel polymer and various concentrations of KCl polymer muds. A linear swell meter test was subsequently conducted to compare the swelling reduction performance of each mud type. The methylene blue test results indicated a smectite content of 60 meq/100 g, confirming the presence of reactive clay in the 26-inch borehole. LSM test results showed that the Gel Polymer mud exhibited 25.78% swelling over 11 hours, indicating it was ineffective for such formations.In contrast, the 7% KCl Polymer mud significantly reduced swelling to 16.38% over 8 hours. This improvement is attributed to the substitution of Na⁺ ions with K⁺ ions, which neutralizes negative charges on clay surfaces and reduces the clay's water-holding capacity. The findings confirm that KCl Polymer mud is more effective in minimizing clay swelling in reactive geothermal formations.